Analysis of energy efficient heat and lighting systems in a subarctic greenhouse - Sigvardsson, William (Luleå tekniska universitet, Institutionen för teknikvetenskap och matematik, 2023)
This report studies a subarctic greenhouse located in Nikkala, Sweden called Nikkala handelsträdgård. Through a visit to the greenhouse coupled with the creation of two simulation models this study investigates the differences in energy demand with water-carried and air-carried heating systems, high pressure sodium lights and Light emitting diode lights and insulation in parts of the greenhouse without a active cultivation. With the purpose of comparing the alternatives to the existing system at Nikkala handelsträdgård. This, to evaluate if an investment in insulation for the non cultivating parts or changing to a water-carried heating system with Light emitting diode lights could be considered profitable. Operating a greenhouse in a subarctic climate is a hard task and especially if the operation is year round. Efficient heating systems, thermal screens, dehumidifying measures and Lighting systems are crucial to ensure a profitable business. At Nikkala handelsträdgård they are currently using a pellets burner in combination with a air-carried heating system and HPS lamps in the majority of the greenhouse. The simulations of the main greenhouse were made in Ansys fluent where the crop section was simulated by implementing source terms to a macro porous medium. The parts of the greenhouse which did not host an active cultivation were simulated in IDA ICE. It was found that saving of just under 14 800 SEK monthly or 18 % could be made by implementing a water-carried heating system in combination with state of the art lighting. Given this a payback-time of 3-9 years could be expected given different scenarios. An implementation of insulation in the non cultivation greenhouse parts would save up to 25 300 SEK annually or 46 % of the heat demand and the investment would give a payback-time of 1-2 years given different scenarios. Given this a reduction of CO2 equivalents of just under 1,9 tonnes could be achieved yearly. It was concluded that relatively inexpensive investments could have a great impact on the energy ...